OPTIMALISASI PERAN BALAI PEMASYARAKATAN DALAM MELAKUKAN PEMBIMBINGAN DAN PENGAWASAN BAGI NARAPIDANA ASIMILASI RUMAH DIMASA PANDEMI COVID-19 - Mustika Amalia (Universitas Muhammadiyah Tapanuli Selatan, 2021)
Terrorism is included in an extraordinary crime which is very worrying because it threatens the community with various actions that are taken. The existence of deradicalization as a guidance program that changes the radical nature of terrorism convicts makes their hopes for the government in member terrorism crimes. With this de-radicalization program, it is hoped that the terrorists can change and be able to reunite with society. But to make this happen, a comprehensive order is needed for terrorism convicts who have undergone a deradicalization program in order to foster public trust. The method used in this research is a qualitative method by collecting literature or collecting reading material and references related to the subject matter. The results of the research show how the deradicalisation program of terrorism convicts is taking place in order to prepare them to reintegrate into society.